Excavating the data pit: the Portuguese Parish Memories (1758) as a gold standard - Santos, Ivo (2020)
The common approach to research in History and Archaeology tends to the continuous development of new databases, completely independent of each other with the consequence of data fragmentation, atomisation of knowledge, and ultimately the creation of data silos. This happens because of academic tradition, but also because these disciplines work with fragmented information to understand historical data, the contexts, which enables the creation of multiple narratives and interpretations. However, for these disciplines, the context is a key aspect that always should be preserved. The Memórias Paroquiais (Parish Memories) correspond to a survey, organized in 3 major parts (land, mountain and river) and are an essential source for obtaining a radiography of Portugal in 1758-1761. We believe that this primary source could reach a new exponent if worked from a different approach: semantically annotated, processed and modeled. We propose that the Portuguese Parish Memories, due to their intrinsic characteristics, should constitute a Knowledge Base (KB) to connect with other historical sources and research outputs. Ultimately, the Parish Memories could be a Gold Standard for the Natural Language Processing with impact on the research on other historical sources of Early Modern History Portugal, regardless of the knowledge domain.